2004
DOI: 10.1016/j.pbiomolbio.2003.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Glutamate-induced deregulation of calcium homeostasis and mitochondrial dysfunction in mammalian central neurones

Abstract: Delayed neuronal death following prolonged (10-15 min) stimulation of Glu receptors is known to depend on sustained elevation of cytosolic Ca(2+) concentration ([Ca(2+)](i)) which may persist far beyond the termination of Glu exposure. Mitochondrial depolarization (MD) plays a central role in this Ca(2+) deregulation: it inhibits the uniporter-mediated Ca(2+) uptake and reverses ATP synthetase which enhances greatly ATP consumption during Glu exposure. MD-induced inhibition of Ca(2+) uptake in the face of cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
90
0
10

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(107 citation statements)
references
References 185 publications
7
90
0
10
Order By: Relevance
“…Mitochondrial dysfunction could result in an increase in the sensitivity of neurons to glutamate, leading to Ca 2ϩ induced cellular dysfunction and eventually cell death (the role of mitochondria in excitotoxicity is discussed in Refs. [43][44][45]. It has been shown previously that decreases in oxidative phosphorylation and state 3 rates are early events in excitotoxicity, and occur prior to the commitment to cell death (46).…”
Section: Discussionmentioning
confidence: 96%
“…Mitochondrial dysfunction could result in an increase in the sensitivity of neurons to glutamate, leading to Ca 2ϩ induced cellular dysfunction and eventually cell death (the role of mitochondria in excitotoxicity is discussed in Refs. [43][44][45]. It has been shown previously that decreases in oxidative phosphorylation and state 3 rates are early events in excitotoxicity, and occur prior to the commitment to cell death (46).…”
Section: Discussionmentioning
confidence: 96%
“…Stimulation of glutamate receptors in chick RGCs in vitro caused calcium influx through NMDA receptorassociated channels and subsequently their death. Increased calcium influx in the neurons causes mitochondrial dysfunction and nNOS generation resulting in neuronal cell death [103,104]. We have shown that expression of nNOS in the RGCs is enhanced in hypoxic injury and that hypoxic induction of nNOS is mediated by nuclear factor kappa B (NF-κB).…”
Section: Hypoxia and Glutamatementioning
confidence: 99%
“…(11) Other oxidants inactivate the plasma membrane calcium-ATPase, leading to increased levels of intracellular calcium [44][45][46][47][48]; such inactivation of the calcium ATPase has substantial pathophysiological effects [45][46][47][48] and may well contribute to the prolonged impairment of calcium extrusion seen under circumstances, where the NO/ONOO − cycle may have a role [49][50][51].…”
Section: �� �� ��Eci�c ������� − Cycle Mechanismsmentioning
confidence: 99%
“…(13) While modest elevation of mitochondrial calcium, leads to increased ATP synthesis, substantial elevation of intracellular calcium leads to substantial increases in intramitochondrial calcium, leading to increased superoxide generation in the mitochondrion [49][50][51]53]; large increases in mitochondrial calcium will lead, in some circumstances, to apoptotic cell death [50,51,53]. (14) Intracellular calcium stimulates the nNOS and eNOS forms of nitric oxide synthase, both of which are calcium-dependent enzymes.…”
Section: �� �� ��Eci�c ������� − Cycle Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation